Imaging in connective tissue disease-associated interstitial lung disease - Praveen P G. Rao; Kushal Joshi; Sidath Liyanage; Daniel Dalili; Gouri Koduri (Indian Journal of Rheumatology)
Interstitial lung disease (ILD) in rheumatic or connective tissue disease (CTD) is well recognized and presents both diagnostic and management challenges to rheumatologists. Imaging plays a central role in diagnosing and assessing treatment response. Chest radiography is easily available and is usually the first imaging modality but is neither sensitive nor specific. Lung ultrasound (LUS) is an emerging modality to detect the presence and assess the evolution of ILD. There are established correlations of B-lines and subpleural interlobular septal thickening in ILD. LUS could be a useful tool in the early screening of younger patients at risk of ILD and in minimizing cumulative radiation exposure. High-resolution computed tomography (HRCT) remains the modality of choice in characterization, assessment of disease severity/progression, and response to therapy. Interpretation of HRCT in ILD is often challenging, but an emphasis on pattern recognition in the clinical context should lead to prompt diagnosis and management. The most common ILD pattern in rheumatic disease is nonspecific interstitial pneumonitis followed by usual interstitial pneumonitis. Other less common but well-recognized patterns are organizing pneumonia, lymphocytic interstitial pneumonitis, diffuse alveolar damage, and disease-modifying antirheumatic drug-related pneumonitis. A systematic approach with a focus on the dominant pattern, zonal distribution, and additional specific features such as necrobiotic nodules (rheumatoid arthritis) and dilated esophagus (systemic sclerosis) should, in a majority of the cases, lead to the right diagnosis. Comparison with any prior imaging and follow-up imaging aids diagnostic confidence and can prognosticate disease outcome. This article aims at describing the established CTD-ILD patterns and diseases with a pictorial review and emphasizes on emerging LUS technique.